Research on Nanosecond High-Pulse-Energy Regenerative Amplifier with Adjustable Pulse Duration and Third Harmonic Generation - Mengyao Cheng; Hua Wang; Wenlong Tian; Yizhou Liu; Jiangfeng Zhu (Photonics)
We reported on a nanosecond regenerative amplified laser with a repetition rate of 1 kHz by employing laser diodes (LDs) with distinct wavelengths as both the seed laser and the pump source and utilizing Nd:YAG as the gain medium. The single-pulse energy was 1.58 mJ and the pulse duration was adjustable, ranging from 1 to 5 ns. Combining two oppositely oriented BBO crystals for second harmonic generation (SHG) and an LBO crystal for third harmonic generation (THG), a 355 nm laser with a single-pulse energy of 257 μJ was attained, corresponding to a THG efficiency of 16.2%.